Neutralization of Toxic Malodorous Gases from Cattle Slurry - Katarzyna Kotarska; Wojciech Dziemianowicz; Anna Świerczyńska; Michał Lach; Barbara Sokołowska (Applied Sciences, 2025)
This study investigated the ability of bacterial strains to neutralize odorous substances from cattle slurry (CS). The research was performed to develop a microbial preparation for the deodorization of CS. Among the strains of bacteria (Bacillus and Pseudomonas) isolated from natural environments, those with the highest ammonia and hydrogen sulfide reduction were selected, and the bacterial consortium was prepared. The biopreparation reduced ammonia by 98% in the unshaken culture and 100% in the aeration culture, after 10 days of incubation (compared to the initial sample). Complete elimination of hydrogen sulfide was noted on day 6 of the deodorization process for both cultures. The microbiological supplementation also had a positive effect on the chemical composition of the slurry, increasing its fertilizer value. The addition of biopreparation to the slurry resulted in a reduced loss of ammonium ions and increased nitrogen concentration by 29%. It was found that the use of the microbial consortium also increased the availability of potassium and phosphorus, which can be used in agricultural production. Nitrogen retention by microorganisms in the slurry increases its organic value and leads to a reduction in the use of mineral fertilizers.